2020
DOI: 10.1002/ece3.6064
|View full text |Cite
|
Sign up to set email alerts
|

Small fish, large river: Surprisingly minimal genetic structure in a dispersal‐limited, habitat specialist fish

Abstract: Genetic connectivity is expected to be lower in species with limited dispersal ability and a high degree of habitat specialization (intrinsic factors). Also, gene flow is predicted to be limited by habitat conditions such as physical barriers and geographic distance (extrinsic factors). We investigated the effects of distance, intervening pools, and rapids on gene flow in a species, the Tuxedo Darter (Etheostoma lemniscatum), a habitat specialist that is presumed to be dispersal‐limited. We predicted that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 138 publications
0
3
1
Order By: Relevance
“…Contemporary population structure can impact the spread of adaptive genetic variation through evolutionary processes such as gene flow or genetic drift (Lande, 1976; Slatkin, 1987; Tigano & Friesen, 2016; Willi et al., 2006). Despite the fine‐scale scope of our study, we did find some evidence of population structure, which contrasts to similar darter studies that found no discernable genetic structure (Davis et al., 2015; Washburn et al., 2020). The two genetic clusters identified did not correspond to geographic stream distance.…”
Section: Discussioncontrasting
confidence: 99%
“…Contemporary population structure can impact the spread of adaptive genetic variation through evolutionary processes such as gene flow or genetic drift (Lande, 1976; Slatkin, 1987; Tigano & Friesen, 2016; Willi et al., 2006). Despite the fine‐scale scope of our study, we did find some evidence of population structure, which contrasts to similar darter studies that found no discernable genetic structure (Davis et al., 2015; Washburn et al., 2020). The two genetic clusters identified did not correspond to geographic stream distance.…”
Section: Discussioncontrasting
confidence: 99%
“…Simple models of such systems predict asymmetric gene flow and higher genetic diversity in downwind, downstream, and down‐current locations compared to source populations. In rivers, we expect the accumulation of genetic diversity from the headwater to downstream locations in a one‐dimensional linear stepping‐stone pattern (Maruyama, 1969; Thomaz et al, 2016; Washburn et al, 2020). However, numerous factors could cause deviations from this expectation, including the presence of barriers to gene flow and corridors or other landscape complexities that promote multidirectional gene flow (Petkova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Darter ecology and reproductive behaviour may also play a key role in maintaining population structure, as these fishes can have strong preferences for specific microhabitats (Alexander & Phillips, 2012) and sexual traits (Williams & Mendelson, 2011). Not all darters exhibit a strong signal of population structure, suggesting that the potential for diversification is a result of particular combinations of life historical, anthropogenic, and biogeographic conditions (Camak & Piller, 2018; Washburn et al, 2020). Here, the picture of freshwater fish diversification becomes local, complex, and contingent rather than general, unimodal, and singular (Mayden, 1988; Near & Keck, 2005).…”
Section: Discussionmentioning
confidence: 99%